2008
DOI: 10.1007/978-3-540-92219-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Speech Recognition Based on Electromyographic Biosignals

Abstract: Abstract. This paper presents our studies of automatic speech recognition based on electromyographic biosignals captured from the articulatory muscles in the face using surface electrodes. We develop a phone-based speech recognizer and describe how the performance of this recognizer improves by carefully designing and tailoring the extraction of relevant speech feature toward electromyographic signals. Our experimental design includes the collection of audibly spoken speech simultaneously recorded as acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When considering a method that provides artificial communication to a speech-deprived individual, one must identify the most efficient means given the nature of the individual’s impairment. Some methods rely on non-vocalized articulator movements or other sub-vocalizations (Betts and Jorgensen, 2006; Fagan et al, 2008; Jorgensen et al, 2003; Jou et al, 2006; Jou and Schultz, 2009; Maier-Hein et al, 2005; Mendes et al, 2008; Walliczek et al, 2006; Wand and Schultz, 2009) which can be helpful for speech deprived individuals (e.g. laryngectomy patients).…”
Section: Section 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering a method that provides artificial communication to a speech-deprived individual, one must identify the most efficient means given the nature of the individual’s impairment. Some methods rely on non-vocalized articulator movements or other sub-vocalizations (Betts and Jorgensen, 2006; Fagan et al, 2008; Jorgensen et al, 2003; Jou et al, 2006; Jou and Schultz, 2009; Maier-Hein et al, 2005; Mendes et al, 2008; Walliczek et al, 2006; Wand and Schultz, 2009) which can be helpful for speech deprived individuals (e.g. laryngectomy patients).…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…Current methods for silent speech available to neurologically normal individuals or those with damaged vocal tracts typically involve the placement of surface electromyographic (EMG) electrodes on the orofacial and laryngeal speech articulators (Betts and Jorgensen, 2006; Fagan et al, 2008; Jorgensen et al, 2003; Jou et al, 2006; Jou and Schultz, 2009; Maier-Hein et al, 2005; Mendes et al, 2008; Wand and Schultz, 2009). Electrical recordings are transmitted from the electrodes to an analysis computer which has been trained to recognize a small vocabulary of words based upon the speaker’s EMG pattern.…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…This TD feature set was originally proposed by [28], [29] and has been used to convert speech-related EMG to acoustic speech in several works, such as [9], [30], and [7].…”
Section: Feature Extractionmentioning
confidence: 99%
“…Kübler et al [43] reported a strong correlation between physical impairment and BCI performance (Figure 7). Some methods rely on non-vocalized articulator movements or other sub-vocalizations [40][41] [42] which can be helpful for speech deprived individuals (e.g. laryngectomy patients).…”
Section: Bci Applicationsmentioning
confidence: 99%